Piezo-generated charge mapping revealed through direct piezoelectric force microscopy - A. Gomez (Nature Portfolio, 2017)
Piezoelectrics and ferroelectrics are important for everyday applications, but methods to characterize these materials at the nanoscale are lacking. Here the authors present direct piezoelectric force microscopy, an AFM mode that can measure charges generated by the direct piezoelectric effect with nanoscale resolution.